2003
DOI: 10.1093/brain/awg026
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical correlates of dyslexia: frontal and cerebellar findings

Abstract: In this study, we examined the neuroanatomy of dyslexic (14 males, four females) and control (19 males, 13 females) children in grades 4-6 from a family genetics study. The dyslexics had specific deficits in word reading relative to the population mean and verbal IQ, but did not have primary language or motor deficits. Measurements of the posterior temporal lobe, inferior frontal gyrus, cerebellum and whole brain were collected from MRI scans. The dyslexics exhibited significantly smaller right anterior lobes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
194
6
14

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(229 citation statements)
references
References 72 publications
15
194
6
14
Order By: Relevance
“…Differences in non-cortical regions included the hippocampus/parahippocampus, amygdala, globus pallidus and putamen. These brain regions correlate with areas identified previously as being involved in reading and/or symbol decoding either structurally or functionally (Kronbichler et al 2007;Brambati et al 2006;Cao et al 2006;Casanova et al 2005;Silani et al 2005;Vinckenbosch et al 2005;Aylward et al 2003;Eckert et al 2003;Ruff et al 2003;Brown et al 2001;Eliez et al 2000;Rumsey et al 1999). …”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Differences in non-cortical regions included the hippocampus/parahippocampus, amygdala, globus pallidus and putamen. These brain regions correlate with areas identified previously as being involved in reading and/or symbol decoding either structurally or functionally (Kronbichler et al 2007;Brambati et al 2006;Cao et al 2006;Casanova et al 2005;Silani et al 2005;Vinckenbosch et al 2005;Aylward et al 2003;Eckert et al 2003;Ruff et al 2003;Brown et al 2001;Eliez et al 2000;Rumsey et al 1999). …”
Section: Discussionsupporting
confidence: 73%
“…Compared to structural imaging studies before 2005 (Brambati et al 2004;Eckert et al 2003;Brown et al 2001;Eliez et al 2000), several recent studies, using more optimized and contemporary imaging techniques, have reported mixed patterns of increased and decreased gray matter volumes in dyslexia. More specifically, these studies show increases in GM volume in several cortical areas pertaining to language including: posterior, medial and inferior temporal gyri, precentral and postcentral gyri, superior and medial frontal gyri and precuneus (Kronbichler et al 2007;Silani et al 2005;Vinckenbosch et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…They are also consistent with studies that have found abnormal cerebellar morphology or activity in patients with developmental dyslexia and language impairment. Structural MRI studies have shown that the right anterior lobe of the cerebellum is smaller in children with developmental dyslexia and is correlated with reading performance (Eckert et al, 2003). Another structural MRI study reported smaller cerebellar grey matter asymmetry in adults with developmental dyslexia and that smaller asymmetry was correlated with poorer reading performance (Rae et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Since RD subjects would be expected to have a greater likelihood of temporal lobe anomalies [16,17], the observation that the relationships between temporal lobe structures in RD are more similar to those with autism is not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…Temporal lobe differences have been reported in subjects with a reading deficit (RD) when compared to typical developing, non-reading impaired controls [16,17]. Furthermore, some have categorized features of the broader phenotype of language impairments in autism as having commonalities with verbal-based learning disabilities [18,19].…”
Section: Introductionmentioning
confidence: 99%